Appraisal of anti-arthritic and nephroprotective potential of Cuscuta reflexa - Alamgeer; Samia Gul Niazi; Ambreen Malik Uttra; Muhammad Naeem Qaiser; Haseeb Ahsan (Taylor & Francis Group, 2017)
Context: Cuscuta reflexa Roxb. (Cuscutaceae) has been used traditionally for treating sore knees and kidney problems, but its efficacy has not been scientifically examined in treating arthritis and nephrotoxicity. Objective: Present study determines antiarthritic and nephroprotective potential of the aqueous methanolic extract of Cuscuta reflexa (AMECR). Materials and methods: Antiarthritic activity of Cuscuta reflexa in formaldehyde and turpentine oil-induced rat arthritis models was appraised at 200, 400 and 600 mg/kg doses for 10 days and 6 h period, respectively, and in vitro protein denaturation (bovine serum albumin, egg albumin) inhibition was studied at 25-800 μg/mL concentration. The nephroprotective effect involved gentamicin-induced nephrotoxicity in rats at 200, 400 and 600 mg/kg doses. Results: Plant extract at 600 mg/kg significantly reduced paw oedema and joint swelling with maximal inhibition of 71.22% at the 6th hour for turpentine oil and 76.74% on 10th day for formaldehyde. Likewise, in vitro results corroborated significant concentration-dependent increase in percentage protection at 800 μg/mL against both bovine serum albumin (89.30%) and egg albumin (93.51%) denaturation. Similarly, 600 mg/kg dose showed maximum nephroprotection by reducing serum urea (41.400 ± 0.510 mg/dL), uric acid (0.740 ± 0.032 mg/dL), blood urea nitrogen (18.370 ± 0.328), creatinine (3.267 ± 0.076) and minimizing kidney weight gain (0.586 ± 0.005) and histopathological alterations on 8th day. Furthermore, phytochemical and HPLC analysis revealed the presence of important phytoconstituents. Discussion and conclusions: These results suggest that AMECR provides protection against arthritis and nephrotoxicity that might be due to the existence of phytoconstituents, thus supporting folkloric claim.